Understanding Health Inequalities and Justice : New Conversations across the Disciplines - Walker, Rebecca L.; Rivkin-Fish, Michele R.; Buchbinder, Mara (Book collections on Project MUSE., 2016)
"Amid ongoing debate about health care reform, the need for informed analyses of U.S. health policy is greater than ever. The twelve original essays in this volume show that common public debates routinely bypass complex ethical, sociocultural, historical, and political questions about how we should address ideals of justice and equality in health care. Integrating perspectives from the humanities, social sciences, medicine, and public health, the contributors illuminate the relationships between justice and health inequalities to complicate and enrich debates often dominated by simplistic narratives"--